1999
DOI: 10.1109/71.744844
|View full text |Cite
|
Sign up to set email alerts
|

Multidestination message passing in wormhole k-ary n-cube networks with base routing conformed paths

Abstract: This paper proposes multidestination message passing on wormhole k-ary n-cube networks using a new base-routing-conformed-path (BRCP) model. This model allows both unicast (single-destination) and multidestination messages to co-exist in a given network without leading to deadlock. The model is illustrated with several common routing schemes (deterministic, as well as adaptive), and the associated deadlock-freedom properties are analyzed. Using this model a set of new algorithms for popular collective communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 26 publications
1
60
0
Order By: Relevance
“…After path selection, the intermediate destinations perform absorb-and-forward operations along the path. Hamilton path-based algorithm [5] and the Base Routing Conformed Path (BRCP) approach [1] are examples of path-based algorithms utilizing absorb-and-forward property at hardware layer.…”
Section: Broadcast Operationmentioning
confidence: 99%
“…After path selection, the intermediate destinations perform absorb-and-forward operations along the path. Hamilton path-based algorithm [5] and the Base Routing Conformed Path (BRCP) approach [1] are examples of path-based algorithms utilizing absorb-and-forward property at hardware layer.…”
Section: Broadcast Operationmentioning
confidence: 99%
“…Ensuring a scalable implementation of a wide variety of parallel applications necessitates efficient implementation of multicast communication. In general, the literature outlines three main approaches to deal with the multicast problem: unicast-based [1], [3], tree-based [3], [17], and path-based [2], [3], [8], [14], [15], [18]. A number of studies have shown that path-based algorithms exhibit superior performance characteristics over their unicast and tree-based counterparts [2], [14], [15], [18].…”
Section: Introductionmentioning
confidence: 99%
“…In path-based multicast, when the flits of a message reach one of the destination nodes in the multicast group, they are copied to local memory while they continue to flow through the node to reach the other destinations [2], [3], [8], [18]. The message is removed from the network when it reaches the last destination in the multicast group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations